2020
DOI: 10.4103/aer.aer_2_20
|View full text |Cite
|
Sign up to set email alerts
|

Sternomental distance ratio as a predictor of difficult laryngoscopy: A prospective, double-blind pilot study

Abstract: Background: No single test has shown to be an accurate predictor of difficult laryngoscopy. Aims: This study aims to evaluate the effectiveness of the ratio of the sternomental distance (SMD) in neutral and full neck extension position SMD ratio (SMDR) as a predictor of difficult laryngoscopy and any need of assisted intubation. Settings and Design: Prospective, double-blind pilot study. Materials and Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The anesthesiologists always need to prepare for difficult ventilation and intubation especially in morbid patients. Kopanaki et al [ 14 ] and Prakash et al [ 15 ] found that sternomental distance was one of conventional parameters of airway assessment. We found that thyromental distance and sternomental distance predicted difficult laryngoscopy among obese Thai patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthesiologists always need to prepare for difficult ventilation and intubation especially in morbid patients. Kopanaki et al [ 14 ] and Prakash et al [ 15 ] found that sternomental distance was one of conventional parameters of airway assessment. We found that thyromental distance and sternomental distance predicted difficult laryngoscopy among obese Thai patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that SMDD provides a rapid, simple, objective measure for predicting patients at risk of DLV. Another recent study conducted by Kopanaki E et al in 2020 19 included 221 surgical patients with a mean BMI of 27.1±5.1 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic arrest is the worst complication which can be happened if we cannot secure the patients' airway even we follow the guidelines of Difficult Airway Society Guidelines (DAS) 14 and Practice guidelines for management of the difficult airway reported by American Society of Anesthesiologists(ASA). 15 Kopanaki et al 16 and Prakash et al 17 found that sternomental distance was one of conventional parameters of airway assessment to predict difficult laryngoscopy among obese patients. We found that thyromental distance and sternomental distance predicted difficult laryngoscopy among obese Thai patients.…”
Section: Discussionmentioning
confidence: 99%